The effects of dialysis on body bioimpedance / Nurulnisa Nor Azman - Nurulnisa , Nor Azman (2012)
Recently, hemodialysis has been chosen as a treatment-of-choice for individual which having the kidney problem or kidney impairment. The dialysis machine which works based on the principle of diffusion of solutes (sodium, potassium, urea, etc) and water content through the semipermeable membrane. It removes any wastes in the blood and the excessive water in the body so that body could maintain its fluid and the body composition. The effectiveness of the dialysis treatment to the human body can be determined through the technique known as Bioelectrical Impedance Analysis (BIA) that is inexpensive, non-invasive and promising method. BIA is frequently employed technique to measure the parameter include Resistance and Reactance, mass distribution such as Body Cell Mass, Extracellular Cell Mass, Lean Body Mass, Fat Mass, Body Mass Index (BMI) and Basal Metabolic Rate (BMR). It also can be used to determine the water compartments of the body which includes Intracellular Water, Extracellular Water and Total Body Water (TBW). This technique involved the application of small current through the human body by using four surface electrodes. This measurement was conducted on 50 patients with kidney problem that underwent for the dialysis treatment at the Dialysis Center. The body bioimpedance parameters were measured by using the impedance analyzer before and after the dialysis treatment. The data obtained was analyzed by using the commercial statistical software, Statistical Package for the Social Sciences (SPSS). The ANOVA and paired t-test were conducted to compare the result before and after the dialysis treatment. The result showed that there was an improvement of body bioimpedance parameters after the patient receiving the dialysis treatment. BIA analysis provides an important understanding as a measurement tool to study about the body composition and physiology during the dialysis treatment. In addition, this analysis can be used to monitor and evaluate the body bioimpedance directly. It also can contribute to the better planning and strategies to have an effective dialysis treatment so that the patient which receiving the dialysis treatment would have great value of body bioimpedance and healthy lifestyle.